Heating and electricity expenses: Saving incentives not impacting basic income recipients - Lars Felder; Peter Haan; Stefan Bach; Wolf-Peter Schill (DIW Weekly Report, 2023)
Basic income benefits cover recipients' actual heating expenses as long as they are not unusually high. In contrast, their electricity expenses are only covered via a lump sum at the standard rate. Thus, basic income recipients have weaker incentives for reducing their heating expenses than for reducing their electricity expenses. Using Socio-Economic Panel (SOEP) data, it can be seen that basic income households have higher electricity bills despite this incentive: On average, they spend five euros more on heating and nine euros more on electricity than comparable households not receiving basic income. These higher bills may be due to a lack of sufficient information about their expenses and ways to save energy, or they are unable to save due to non-energy efficient electrical appliances and longer attendance time at home. These interrelationships need to be taken into consideration when drawing up a climate policy that aims to provide savings incentives by increasing the CO2 price; such a policy can only be effective if households are able to react to price incentives. Thus, in addition to increasing the CO2 price, targeted subsidy programs for energy efficiency measures as well as information campaigns for households are needed.
Keywords: Q41; H53; D31; 330; energy cost; heating cost; income distribution; social transfers